ANALISIS BENTUK DAN MAKNA RAGAM BAHASA LISAN INFORMAL DALAM PERCAKAPAN ACARA TALK SHOW JEPANG SHABEKURI007 - a, Susanti (Humanis; Volume 2. No. 1. Januari 2013)
This research was done to find out the kinds of spoken language that appeared on Japanese TV show called SHABEKURI007. There are two problems in this research, the first is the forms of the spoken language on Japanese conversation and the second is the contextual meaning of the spoken language contained on Japanese TV show called SHABEKURI007. The theories used in this research are the spoken language theory by Tomisaka (1996), and the theory of contextual meaning by Suwandi (2008). The research was done trough three phases, the first is collecting data, the second is analyzing data and the last was presenting the result of the research. The source for the data of this research was the conversation that appeared during the Japanese TV show SHABEKURI007. The Method and technique of collecting the data that used is the referring method while the inductive method used to analyzing the data. The presenting method done by using the informal method. After analyzed, the data showed the forms of Japanese spoken language divided in six kinds that are Joshi no Shouryaku, Tanshukuku, Kimarimonku, Kurikaeshi, Aimai Hyougen, and Gojun no Henka. The contextual meaning contained on the Japanese informal spoken language appeared on the Japanese TV show SHABEKURI007 as a connection between the speech and the situation so the contained meaning on the conversation depends on the situation that occur.
Keywords: spoken language, contextual meaning, sentence pattern